Schistosomiasis in Benin (West Africa): epidemiology and ecology of the host-parasite interactions - (:unkn) unknown (My University, 2006)
This work presents an epidemiological and an ecological study of schistosomiasis in Benin.At the epidemiological level, a bibliographical summary of the state of work carried out on schistosomiasis in the area of ​​the Economic Community of West African States (ECOWAS) was reported. In Benin, our epidemiological analyzes confirmed the existence of two species of human schistosomes: S. haematobium and S. mansoni out of the five reported in the ECOWAS region in which Benin is located (S. haematobium, S. mansoni , S. guineensis, S. bovis and S. curassoni). The general prevalence obtained for S. haematobium is 85% and that of S; mansoni is 30% with the existence of foci of mixed transmission. Malacological surveys revealed the presence in Benin of at least five species of mollus that five vectors B. forskalii, B. globosus and B. truncatus, vectors of S. haematobium, B. pfeifferi, vector of S. mansoni and I. exustus , an exotic mollusk in Benin, known as a vector of S. indicum, S. spindale and S. nasale in Southeast Asia. We report the presence of I. exustus for the first time in Benin where this mollusk seems to be, for the moment, passive in the transmission of schistosomiasis.In terms of the ecology of mollusc-parasite interactions, our study has shown that the different populations of S. haematobium are differently compatible with three of the four groups of Bulinus molluscs: the africanus group, the forskalii group and the reticulatus group while the different populations of S. mansoni are all also compatible with B. pfeifferi. The analysis of six life history traits, prepatent period, prevalence, cercarial production in the parasite and growth, reproduction and survival of molluscs was approached with five local populations of schistosomes including three populations of S. haematobium (Doh, Sô -Tchanhoué and Toho-Todougba) and two populations of S. mansoni (Kpinnou and Toho-Todougba) and revealed that while the populations of S. haematobium appe
Keywords: African Research